Totally laparoscopic surgery for a hydrocele of the canal of Nuck extending from the abdominal cavity to the subcutaneous space: a case report - Kenichi Nakamura; Takahiko Higashiguchi; Yuko Chikaishi; Kazuhiro Matsuo; Tomoyoshi Endo; Koji Morohara; Kenji Kikuchi; Susumu Shibasaki; Hidetoshi Katsuno; Ichiro Uyama; Koichi Suda; Zenichi Morise (Surgical Case Reports)
Abstract Background Hydrocele of the canal of Nuck (HCN) is a rare disease, and its indications for laparoscopic surgery are not well-established. Case presentation A 53-year-old woman was referred to our hospital due to an uncomfortable thumb-sized inguinal mass. Preoperative computed tomography scan and magnetic resonance imaging revealed a hydrocele extending from the abdominal cavity around the left deep inguinal ring via the inguinal canal to the subcutaneous space. The patient was diagnosed with HCN protruding into the abdominal cavity and extending to the subcutaneous space. Laparoscopy can easily access the hydrocele protruding into the abdominal cavity. Furthermore, laparoscopic hernioplasty can be superior to the anterior approach for females. Hence, laparoscopic surgery was performed. After transecting the round ligament of the uterus, a tense 3-cm hydrocele was dissected with it. In order to approach the hydrocele distal to the deep inguinal ring, the transversalis fascia was incised medially to the inferior epigastric vessels. The subcutaneously connected hydrocele was excised from the incision. Then, the enlarged deep inguinal ring was reinforced using a mesh with the laparoscopic transabdominal preperitoneal approach. The patient was discharged 2 days postoperatively. Laparoscopic resection can be more effective for a hydrocele protruding into the abdominal cavity as it facilitates an easy access to the hydrocele. Moreover, laparoscopic resection of a hydrocele extending from the inguinal canal to the subcutaneous space via a transversalis fascia incision can be safer, with low risk of injury to the inferior epigastric vessels. The incised transversalis fascia and the enlarged deep inguinal ring due to the HCN were simultaneously repaired with the laparoscopic transabdominal preperitoneal repair. There are two reports on laparoscopic resection via a transversalis fascia incision for HCNs located between the inguinal canal and the subcutaneous space, which does not require intraperitoneal hydrocelectomy. However, this is the first report on laparoscopic resection of large HCNs protruding into the abdominal cavity and extending beyond the inguinal canal into the subcutaneous space via intraperitoneal hydrocelectomy and a transversalis fascia incision. Conclusions Laparoscopic surgery with transversalis fascia incision can be useful for HCNs extending from the abdominal cavity to the subcutaneous space.